Pergeseran Tradisi Meurup-urup di Muntigunung dalam Perspektif Perlindungan Anak dan Hak Asasi Manusia - Muhammad Nuha Maulana Pasya; Ahdiana Yuni Lestari (Media of Law and Sharia, 2024)
The community's paradigm of sponging activities in Bali certainly points to Muntigunung Hamlet as a sponger-producing hamlet. The problem of Gepeng in Muntigunung Hamlet is one of the anomalies in the response to customs and traditions (meurup-urup) which then develops into an antinomy and takes root to make a new reality in meurup-urup, exacerbated by the economic crush, and the existing ecology makes this problem like uprooting old teak roots. This research uses analysis with anthropological, juridical, logical, and systematic approaches. The results found that the trend of human error capacity that occurs is trying to be handled by the state in the sense of the Regional Government of Karangasem by taking technical measures which in the opinion of the author is a futile step, therefore the government must carry out a model of handling spongers in terms of direct involvement with the handling of camp assessment and social work for adult spongers and in child spongers is given education and the rights attached to it as a society so as not to violate the right to live properly, be educated, free of discrimination and degrading treatment, especially in this case spongers.   Keywords: Tradisi, Meurup-urup, Gepeng, Hukum, Negara.